"Preserved" glucagon secretion in fulminant type 1 diabetes. Issue 1 (9th November 2018) - Murase‐Mishiba, Yuko; Bessho‐Tachibana, Megumi; Imagawa, Akihisa
Abstract : Mixed‐meal tolerance tests were carried out after an overnight fast. Healthy control participants (■), type 1A diabetespatients (○) and fulminant type 1 diabetic patients (▲). Data are presented as the mean ± standard error of the mean.